The experience of working as a nurse during the COVID-19 era - Sari, Arnis Kartika; Ba, May Sein (Universitas Muhammadiyah Magelang, 2022)
The spread of COVID-19 infection is still being an awareness for nurses working in the Hospital. As documented, several nurses were exposed to that infection leading to increased prevalence. To prevent this, innovation must be made to optimize care and reduce infection rates. This clinical experience highlighted the importance of creating personal protective equipment. Also, the recommendation is provided mainly for the stakeholder to increase the production and the availability of that equipment. Keywords: COVID-19; nursing care; clinical experiences; quality of care; awareness